METAL FOAM AND METHODS FOR MAKING METAL FOAM - Patent application
Patent Information
- Application Number
- JP2024549160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2023-02-22
- Publication Date
- 2025-03-21
Smart Images

Figure 2025507611000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous suspension for producing a porous metallic structure, a method for producing a porous metallic material, and uses of such a metallic material. [Background technology]
[0002] Porous metals have long been used as filters in chemical processes and electrodes in functional devices. Steel and iron-based structures with highly tunable porosity have been explored as sustainable, lightweight materials for a variety of structural, biomedical and energy-related applications.
[0003] Porous metals have been used as components in jewellery, filters and batteries [1-2], but have also been explored for structural lightweighting, catalysis, thermal management and tissue regeneration. [3-9] This wide range of established and promising applications is due to the unique set of properties offered by the permeated metal network combined with the light weight and open channels provided by the porous phase.
[0004] By controlling the porosity and pore size of the metal structure, the properties of the porous metal can be tailored to meet the requirements of a particular application. Fabrication techniques have a direct impact on the porosity and pore size of the final structure, and therefore have been investigated to control the properties and functionality of porous materials [10-13].
[0005] The advent of 3D printing has opened up new opportunities for the design and fabrication of novel bioinspired hierarchical porous materials with antagonistic properties unreachable by conventional manufacturing.
[14] This could potentially lead to bone-inspired structures that are both lightweight and mechanically efficient, as well as sponge-inspired filters that combine high efficiency with low pressure drop.
[15]
[0006] 3D printing techniques utilized for the fabrication of porous cellular metals include powder bed melting [16-18], electron beam melting [19-20], various replication techniques [3, 7, 21] and direct ink writing [22-24]. Among the techniques capable of producing large centimeter-scale objects, direct ink writing (DIW) is particularly attractive due to its potential to print complex structures at room temperature using readily available, inexpensive tabletop printers.
[0007] To print cellular porous iron by DIW, metal or metal oxide precursor particles are suspended in a binder-containing liquid phase to produce a viscoelastic ink that is subsequently extruded through a sub-millimeter nozzle [23, 25]. The printed cellular structures are then dried, reduced and sintered to densify the deposited filaments
[26] . The resulting metal structures exhibit open cells, the size and relative proportion of which are a result of the toolpath of the printing nozzle. Despite the biocompatibility, mechanical properties and electrochemical responses that have been demonstrated so far [23, 25], the potential of direct ink writing as a tool to fabricate metals with tailorable hierarchical porous structures has yet to be fully exploited.
[0008] A strategy to control the porosity of materials across multiple length scales is to print inks or resins containing building blocks that generate porosity through a predeterminable self-assembly process [27-29]. In this approach, larger pores created by the toolpath are combined with smaller pores resulting from the self-assembling ink to create structural features below the printer resolution. Air bubbles, liquid droplets or organic particles have been used as self-assembling building blocks to print ceramics and polymers with programmable hierarchical porosity [27, 30-31]. Porous silica-based glasses with tunable multiscale pores have also been created by digital light processing (DLP) of phase-separated resins containing self-assembling monomers and metal alkoxide precursors
[29] .
[0009] GB 339645 discloses a process in which metal oxide powders are suspended in water, more than 1 wt% of a foam generating agent is added, the resulting foam is cast, the cast foam is dried, and the dried foam is reduced to a porous metal. A maximum porosity of 80% is achieved.
[0010] US 2009 / 0325780 A1 discloses the preparation of wet foams exhibiting long-term stability, in which colloidal particles are used to stabilize the gas-liquid interface, said particles being either partially hydrophobic particles from the outset or partially hydrophobized particles having an average particle size of 1 nm to 20 μm.
[0011] US Patent Application Publication No. 2021 / 0130244(A1) discloses another method for making particle-stabilized foam.
[0012] WO 2016 / 187097 A1 discloses particle-stabilized foam ink compositions that can be used for 3D printing of hierarchical layered porous structures by deposition of continuous filaments of particle-stabilized ink. To achieve partial open porosity, dissipative particles including polymers or carbon must be added to the foam ink composition. If a metal foam is desired, the foam ink composition can include metal oxide or metal hydride particles, and a reduction or oxidation step is followed by deposition of continuous filaments and drying.
[0013] C. Kenel et al., Addit. Manuf. 2021, 37, 101637, disclose the fabrication of hierarchically porous metal scaffolds by 3D extrusion and reduction of oxide particle inks with salt-type space holders. Metallic structures with three levels of hierarchical porosity can be printed using an ink containing iron oxide particles as metal precursor and a soluble salt-type holder as a sacrificial template
[32] . This process results in a relatively low porosity (less than 38% for iron).
[0014] A. Verdooren et al., J. Mat. Sc. 2005, 40, 4333, disclose a method for making ceramic foams using precursors containing iron (III) oxide, calcium oxide, aluminum and carbon black in an acidic solution containing 50 wt% aluminum orthophosphate. Foaming is the result of hydrogen gas evolution. A similar method using precursors containing iron (III) oxide, magnesium oxide, aluminum and carbon black is disclosed in A. Verdooren et al., J. Am. Ceram. Soc. 2006, 89, 3101.
[0015] C. Minas et al., Adv. Mat. 2016, 28, 9993 (see 27) disclose a method for making particle-stabilized foams and emulsions of metal oxide particles with closed and open porosity.
[0016] US 2015 / 0035209 A1 discloses a method for shaping metals in which a paste containing metal oxide particles, a polymeric binder and an organic solvent is extruded through a tip to deposit successive layers of the metal oxide paste onto a substrate to form a three-dimensional object. The object is exposed to a reducing gas at a temperature and for a period of time sufficient to reduce and sinter the metal oxide particles to form the three-dimensional metal object.
[0017] WO 2015 / 175880 A1 discloses a 3D printable ink composition comprising metal oxide particles and an elastomeric polymer binder.
[0018] WO 2020 / 243428 A1 discloses a wet foam composition for making sintered open cell ceramic foams.
[0019] US 2006 / 0211802 A1 discloses a method for producing a porous metal-containing material. Particles comprising at least one polymeric material and at least one metal-based compound are dispersed in at least one solvent. The solvent is removed from the composition and the polymeric material is decomposed, thereby converting the solvent-free particles into a porous metal-containing material. [Prior art documents] [Patent documents]
[0020] [Patent Document 1] GB 339645 [Patent Document 2] US Patent Application Publication No. 2009 / 0325780(A1) [Patent Document 3] US Patent Application Publication No. 2021 / 0130244(A1) [Patent Document 4] International Publication No. 2016 / 187097(A1) Brochure [Patent Document 5] US Patent Application Publication No. 2015 / 0035209(A1) [Patent Document 6] International Publication No. 2015 / 175880(A1) Brochure [Patent Document 7] International Publication No. 2020 / 243428(A1) Brochure [Patent Document 8] US Patent Application Publication No. 2006 / 0211802(A1) [Non-patent literature]
[0021] [Non-Patent Document 1] C. Kenel et al., Addit.Manuf.2021, 37, 101637 [Non-Patent Document 2] A. Verdooren et al., J. Mat. Sc. 2005, 40, 4333 [Non-Patent Document 3] C. Minas et al., Adv. Mat. 2016, 28, 9993 Summary of the Invention [Problem to be solved by the invention]
[0022] There is a general need for improvement in this area. [Means for solving the problem]
[0023] A general object of the present invention is to provide improvements in the manufacture of metal foams and porous metal structures.
[0024] In the context of this specification, the terms metal foam and porous metal structure are used synonymously.
[0025] It is an object of the present invention to provide an advantageous aqueous suspension for producing porous metal structures that allows additive manufacturing of three-dimensional objects that can be converted into porous metal structures in a subsequent step.
[0026] Another object of the present invention is to provide a method for making a porous metal material.
[0027] Another object of the present invention is to provide advantageous uses and applications of such porous metal materials.
[0028] These and other objects are substantially achieved by means of the features of the independent claims. Advantageous embodiments and variants are set forth in the dependent claims.
[0029] Further aspects of the invention will become apparent as this description proceeds.
[0030] The invention may include one or more of the features recited in the accompanying claims and / or one or more of the following features and combinations thereof.
[0031] A first aspect of the invention relates to an aqueous suspension of a foam or emulsion for producing a porous metal structure.
[0032] The aqueous suspension according to the present invention is a mixture of 2 to 49 vol. % of at least one compound containing metal atoms, the at least one compound being solid at room temperature and having the form of a powder, suspended in water, and containing 10 -9 The mixture includes a mixture containing 0.1 mol of a surfactant. The aqueous suspension is part of a foam and / or part of an oil-in-water emulsion containing 30-90 vol. % of a lipophilic phase that does not contain a polymerizable compound.
[0033] Such polymerizable compounds may be, for example, monomeric or oligomeric compounds that are susceptible to polymerization under the conditions of subsequent processing steps.
[0034] The amount of surfactant relative to the amount of powdered suspending compound containing metal atoms required to obtain a stable foam depends, among other factors, on the chain length of the surfactant. Long-chain surfactants can result in particle-stabilized foams even when used at very low concentrations. As explained in ARStudart et al., "Unifying Model for the Electrokinetic and Phase Behavior of Aqueous Suspensions Containing Short and Long Amphiphiles," Langmuir 2011, 27, 11835-11844, the concentration of amphiphile required to halve the zeta potential is a good indicator of the minimum concentration required for foaming.
[0035] Such aqueous suspensions according to the invention can be used as stable wet foams or stable emulsions that can be used as inks for additive manufacturing, in particular for direct ink writing. Such wet bodies can then be dried to convert them into green bodies having a pore structure, which can also be subsequently further processed.
[0036] Foamed aqueous suspensions according to the invention can be produced by forming an aqueous suspension with a gas, for example air or preferably an inert gas such as nitrogen gas.
[0037] Such foamed aqueous suspensions according to the invention make it possible to produce mechanically stable metal structures with hierarchical porosity over several orders of magnitude. At a first level, on a macroscopic scale, the porosity is controllably generated in an additive manufacturing process. At a second, smaller level, the porosity is due to the cells of the foamed aqueous suspension. In the micrometer range, a third level of porosity can be found in the walls of the cells of the second level, with holes in the cell walls connecting the cells. As a result, an open pore structure is produced.
[0038] Without wishing to be bound by any particular theory, it is hypothesized that this third level of porosity is the result of a metal atom rearrangement process at high temperatures, for example during a sintering step.
[0039] Emulsified aqueous suspensions according to the invention can be made by emulsifying an aqueous suspension with a lipophilic phase.
[0040] Advantageously, the lipophilic phase of the oil-in-water emulsion is a lipophilic organic solvent, such as n-octane.
[0041] The droplets of such oil-in-water emulsions provide a scaffold for the formation of macropores similar to foam bubbles. Advantageously, the oleophilic organic solvent is chosen so that its boiling point (n-octane: 125-127 °C at atmospheric pressure) is in a higher but similar range to that of water. The printed emulsion-based ink remains mechanically stable upon drying of the printed object, and the organic solvent can be removed in the same step as the water.
[0042] The droplets of such oil-in-water emulsions do not affect the mechanical stability of the dried green body, so there is no need to mechanically stabilize them, for example by polymerization of the droplets. Such polymerization would in fact be considered a disadvantage, since the polymer cannot be completely removed during the subsequent drying step. Advantageously, therefore, the lipophilic phase of the emulsion does not contain any polymerizable compounds, such as, for example, monomeric or oligomeric compounds, which are prone to polymerization during the drying step.
[0043] Advantageously, the particle size of the powdered compound containing metal atoms is between 0.03 and 5 μm.
[0044] Advantageously, the aqueous composition according to the invention is a foam or an emulsion.
[0045] More preferably, the aqueous composition according to the invention is a foam or an oil-in-water emulsion having a solids content of 2 to 49 vol.%.
[0046] Alternatively or additionally, the bubble size of preferred foamed aqueous compositions according to the invention is between 20 μm and 2 mm. Correspondingly, in emulsions based on aqueous suspensions according to the invention, the diameter of the emulsion droplets is between 5 μm and 2 mm.
[0047] Advantageously, in the aqueous suspension according to the invention, one or more of said compounds comprising a metal atom are compounds which are reducible to a metal in a gaseous atmosphere.
[0048] Additionally or alternatively, in the aqueous suspension according to the present invention, one or more of said compounds comprising a metal atom may be a metal oxide, metal hydroxide, metal chloride or metal fluoride.
[0049] For example, the metal atom-containing compound may be an oxide or hydroxide of Fe, Cr, Zn, Al, Mn, Sn, Pb, Co, Ni, Cu, Mo, Ta, or W. Such compounds can be reduced in a hydrogen atmosphere at a temperature between 200 and 800°C.
[0050] Iron oxides, such as magnetite, optionally in combination with NiO and / or Cr2O3, are particularly advantageous as they allow the production of steel foams with the necessary carbon sourced from organic compounds in aqueous suspension.
[0051] AgCl or PdCl2 may be in the form of a metal atom-containing compound and can be reduced under a hydrogen atmosphere at 200-900°C (for AgCl) or 500-800°C (for PdCl2). Porous palladium structures are particularly useful for heterogeneous catalysis.
[0052] Furthermore, MgF2 can be used as a metal atom-containing compound.The porous magnesium structure can be used as a biocompatible bone scaffold.
[0053] The metal structure can be obtained by reducing, and optionally sintering, a dried structure previously additively manufactured with such a suspension.
[0054] The reduction parameters, especially the temperature, depend on the particle size: on the one hand, the reaction rate depends on the surface area and thickness of the particles, and on the other hand, the sintering process can also be carried out in parallel to the reduction process.
[0055] Advantageously, in such an aqueous suspension according to the invention, the metal oxide powder is Fe3O4 or NiO or a mixture thereof. In particular, such a variant of the invention makes it possible to produce iron-containing metal foams and steel foams.
[0056] Even more advantageously, in such an aqueous suspension according to the invention, the particles of the metal oxide powder have an elongated shape, which improves the rheological properties and the stability of the aqueous suspension after foaming.
[0057] In another advantageous variant of the present invention, one or more of the compounds containing metal atoms in the aqueous suspension contain metal hydrides.
[0058] Particularly preferably, the metal hydride is TiH x , PdH x , ZrH x or MgH2.
[0059] In the case of the metal hydrides MH x such as TiH x , PdH x , ZrH x and the like, the parameter x is the absorption ratio of H to M. In the case of Ti and Zr, 0 < x < 2, and in the case of Pd, 0 < x < 1.
[0060] In such a variant of the present invention, a dried structure prefabricated using such a suspension can be exposed to a high temperature at which hydrogen molecules leave the crystal structure of the metal to obtain a metal structure.
[0061] In the case of TiH x , the appropriate temperature range is between 350 and 600 °C. In the case of ZrH x , the appropriate temperature range is between 600 and 1000 °C. In the case of MgH2, the appropriate temperature range is between 200 and 500 °C.
[0062] In another advantageous variant of the present invention, one or more of the metal atom-containing compounds are metal carbonyl compounds.
[0063] Such a variant of the present invention makes it possible to obtain a metal structure by exposing a dried structure prefabricated using such a suspension to a high temperature at which the metal carbonyl decomposes into the metal and carbon monoxide gas.
[0064] Particularly preferably, the metal carbonyl compound is Rh2(CO)8 or Ru(CO)5.
[0065] For Rh2(CO)8, the appropriate temperature range is between 200 and 600° C. For Ru(CO)5, the appropriate temperature range is between 300 and 700° C.
[0066] Advantageously, a cationic surfactant, such as hexylamine, is used as surfactant in the aqueous suspension according to the invention.
[0067] Advantageously, non-ionic surfactants, such as octyl gallate, may also be used as surfactants in the aqueous suspensions according to the invention.
[0068] In the case of hexylamine, an advantageous surfactant concentration is between 0.01 and 0.05 mmol / g. Advantageously, the amount of surfactant is adjusted to the length of the hydrocarbon chain of the surfactant.
[0069] The aqueous suspension according to the invention preferably contains from 0.01 to 20 g / l of binder, depending on density and chain length.
[0070] Particularly advantageously, the binder is methylcellulose, PVA (polyvinyl alcohol) or PVP (polyvinylpyrrolidone) or a mixture thereof.
[0071] The use of such binders can stabilize the foam or emulsion and also temporarily stabilize the dry structure after drying of the printed object.
[0072] A second aspect of the invention relates to a method for making a porous metal material.
[0073] The method according to the invention for producing a porous metal material comprises the steps of: - providing an aqueous suspension according to any one of claims 1 to 8 comprising a mixture of at least one compound containing a metal atom; - foaming said aqueous suspension to convert it into a foam and / or emulsifying said aqueous suspension with a lipophilic compound to convert it into an oil-in-water emulsion containing 30-90 vol. % of a lipophilic phase, free of polymerizable compounds; - forming a three-dimensional structure with said foam or emulsion; - drying the three-dimensional structure to produce a dried structure; - exposing the dried structure to process conditions that convert the compound containing the metal atom into a metal to produce a metal structure; Includes.
[0074] In the method according to the invention, the metal structure is advantageously sintered.
[0075] The method according to the invention has the advantage that small particles (e.g. 0.03-5 μm) of metal-containing compounds can be produced in a more cost-effective manner than metal particles of similar size. Furthermore, such powdered compounds are non-combustible or less flammable than the corresponding powdered metals, and the particle surfaces are less susceptible to oxidation.
[0076] The foaming step can be carried out, for example, by stirring. Alternatively, foaming can be achieved in situ by decomposition of a suitable compound, for example hydrogen peroxide.
[0077] In one advantageous variant of the method according to the invention, one or more of said compounds containing metal atoms are compounds reducible to a metal in a gaseous atmosphere, and the dry structure is reduced by exposure to a reducing atmosphere to give rise to a metal structure.
[0078] More advantageously, the reduction is carried out in an inert gas atmosphere of 0.5-100 vol% H2.
[0079] The temperature at which the reduction process is carried out depends on the metal ions to be reduced. In the case of Fe3O4 as the metal-containing compound, said temperature is advantageously between 600 and 1000°C.
[0080] The resulting iron foam may have an air content of 75-98 vol%. The density of the resulting iron foam may be 0.4-2 g / cm. 2 The relative density can be in the range of 0.03 to 0.5 for lump iron.
[0081] In another advantageous variant of the method according to the present invention, one or more of said compounds containing metal atoms are interstitial metal hydrides, and the dry structure is exposed to a temperature below the temperature at which hydrogen is released as hydrogen gas to produce a metal structure.
[0082] Advantageously, in the method according to the invention described above, the treatment step resulting in the metal structure and the sintering step are carried out in one process step.
[0083] It is also advantageous in the method according to the invention that the three-dimensional structure is formed by additive manufacturing, for example three-dimensional printing.
[0084] In one advantageous variant of the method according to the invention, the surface of the metal structure is hydrophobized or oleophilized, so that the produced metal structure can be used to efficiently absorb oleophilic compounds, such as, for example, oil spills floating on the water surface.
[0085] In another advantageous variant of the method according to the invention, after the reduction step the metal structures are at least partially oxidized.
[0086] A third aspect of the present invention relates to advantageous uses and applications of the porous metal structure according to the present invention.
[0087] The metallic material according to the invention is produced by the method of the invention.
[0088] In an advantageous use according to the invention, such a metallic material according to the invention is used as a resistance heating element.
[0089] When heat is generated in the metal matrix of the material by passing an electric current through the material, the large surface and open cell structure of the porous metal material allows for efficient heating of gases or liquids within the pores of the material, for example, the metal material according to the invention can be used to vaporize liquids by resistive heating.
[0090] In another advantageous use according to the invention, the metallic material according to the invention is used as a cooling element.
[0091] Such advantageous use can be realised by bringing the material into thermally conductive contact with a Peltier element.
[0092] In a further advantageous use according to the invention, the metal material according to the invention is used for absorbing lipophilic substances suspended in water.
[0093] For this use, the metal material is hydrophobized before the corresponding metal foam body is brought into contact with an oleophilic substance, such as oil spilled in water. The hydrophobized surface of the porous metal structure increases the surface tension between the surface and water, thereby retarding the penetration of water into the air-filled portion of the metal foam. The metal foam body, which has a lower overall density than water, floats on the water surface. Oil that comes into contact with the metal foam body is drawn into the pores of the metal foam by the capillary effect of the open cell structure. This allows efficient absorption of the oleophilic substance on the enlarged surface of the metal foam body as well as in the pores and capillaries.
[0094] A metal foam body with its pores completely filled with oil will eventually have an overall density greater than water. The metal foam body will no longer float but will sink. Such hydrophobized metal foam bodies therefore enable the cleaning of oil spills in bodies of water where collection of oil from the surface is difficult or impossible, e.g., offshore. The metal foam body will sink to the bottom along with the absorbed oil and will eventually be covered by sediment.
[0095] For such applications, iron is preferably used as the metal because it is relatively inexpensive and non-toxic.
[0096] Alternatively, the floating metal foam bodies partially filled with oil can be collected from the surface by the use of magnets or sieves.
[0097] In another advantageous use according to the invention, the metallic material according to the invention is used as a heterogeneous catalyst or as a support structure for a heterogeneous catalyst.
[0098] In a further advantageous use according to the invention, the metallic material according to the invention is used as an electrode. To this end, said metallic material, with or without a functional coating, can be used as both a cathode and an anode of batteries, including lithium iron phosphate batteries and iron-air batteries.
[0099] In another advantageous use according to the invention, the metallic material according to the invention is used as a component in alkaline electrolysis. Components which can be produced from said metallic material are anion and proton exchange membranes, proton transport layers and electrodes.
[0100] In another advantageous use according to the invention, the metallic material according to the invention is used as a reservoir for gases, in particular for molecular hydrogen. For example, the metallic material according to the invention can be used for such adsorptive storage of molecular hydrogen or carbon dioxide due to its porosity and the large active surface accessible thereby. Another approach is the use of the metallic material according to the invention for chemically storing molecular hydrogen in an iron / iron oxide based storage cycle.
[0101] In a further advantageous use according to the invention, the metal material according to the invention is used as a filtering element.
[0102] In order to facilitate a more complete understanding of the present invention, reference is now made to the accompanying drawings, in which: These references should not be construed as limiting the present invention, but are intended to be illustrative only, in the following drawings:
[0103] In the following, components that are identical or at least functionally identical are designated by identical or similar reference numbers. [Brief description of the drawings]
[0104] [Figure 1] FIG. 2 is a schematic diagram illustrating the fabrication process of an iron-based hierarchical porous structure according to the present invention. [Diagram 2] FIG. 2 shows strain-controlled oscillatory rheology measurements on foamed aqueous suspensions according to the present invention. [Diagram 3] FIG. 1 illustrates a 3D printing process for forming a wet foam body. [Figure 4] FIG. 6(a) shows the heating protocol of the reduction step applied to the green body of FIG. 5. FIG. 6(b) shows the XRD spectrum of the resulting fully reduced sample. [Diagram 5] FIG. 3 shows the hierarchical pore structure of the green body after 3D printing of the ink of FIG. 2. [Figure 6] FIG. 6 shows the hierarchical pore structure of the metal body after complete reduction of the green body of FIG. 5. [Figure 7] FIG. 1 shows a microstructured iron-based porous structure according to the invention subjected to different process parameters. [Figure 8] FIG. 8 shows measurements of different mechanical properties of the iron-based porous structure of FIG. 7. [Figure 9] FIG. 8 also illustrates the mechanical properties of the iron foam of FIG. 7. (a) Stress-strain curves for a wide range of applied strains, and (b) sample average mechanical properties obtained from the stress-strain data. [Figure 10] FIG. 2 shows the XRD spectrum of a nickel-iron alloy based metal foam (7 wt % Ni, 850° C., 30 hours) according to the present invention having a purely austenitic atomic structure. [Figure 11] FIG. 11 shows an SEM image of the nickel-iron alloy metal foam of FIG. [Figure 12] FIG. 1 shows (a) average relative density, (b) density, (c) compressive modulus, and (d) strength of nickel-iron alloy metal foams having different Ni contents at two different sintering temperatures. [Figure 13] FIG. 13 shows the Weibull distribution of strength for the nickel-iron alloy metal foam of FIG. 12 containing 28 wt% Ni and sintered at 1000° C. for 30 hours. [Figure 14] FIG. 1 shows different examples of iron-based foams according to the invention: from left to right: unreduced magnetite foam, maghemite foam obtained by oxidizing magnetite at 550° C. for 2 hours, 37 wt % maghemite and 63 wt % hematite foam obtained by oxidizing magnetite at 650° C. for 2 hours, sintered hematite foam obtained by sintering at 1000° C. for 2 hours. [Figure 15] FIG. 14 shows the composition of crystalline phases present in the porous iron structure (30 h at 850 °C) after corrosion in phosphate buffer (37 °C) for 1 to 90 days as determined by Rietveld fitted XRD spectra. [Figure 16] FIG. 13 shows SEM images of iron-based porous structure samples sintered at 850° C. for 30 h and then etched in phosphate buffer (37° C.) for 3 days. [Figure 17] FIG. 2 shows (a) compressive modulus and (b) strength of an iron-nickel based metal foam according to the present invention. [Figure 18] FIG. 13 shows the surface area of printed structures prepared from foams containing different percentages of iron oxide particles and heat treated at different reduction / sintering conditions. [Figure 19] FIG. 14 shows SEM images of printed structures prepared from metal foams containing different percentages of iron oxide particles and heat treated at different reduction / sintering conditions. [Figure 20]Resistive heating of iron-based foam to vaporize liquids. (a) Time-lapse infrared image of 35% Fe foam (5.6 Ω at room temperature) energized with 3 W power. (b) Average temperature profile of the area marked in (a), with the time of the snapshot in (a) indicated by the dotted line in (f). (c) Optical and thermal images (small image at bottom right) of on-demand liquid evaporation by resistive heating using foam infused with ethereal oil (limonene, 0.4 mL / g). [Figure 21] FIG. 1 shows low density (<1 g / cm3), iron-based foam elements surface modified with hydrophobic fumed silica to absorb oil suspended in water. [Figure 22] FIG. 1 shows SEM images of metal foams made by 3D printing of emulsion-based inks (a) after printing and (b) before sintering. [Diagram 23] FIG. 1 shows plots of stress-strain measurements of iron-nickel based metal foams. [Figure 24] FIG. 1 shows the relative compressive modulus versus relative density of different metal foams after first and second measurements. [Diagram 25] FIG. 1 shows different aspects of measurements relating to the novel stiffening effect of metal foams according to the invention. [Figure 26] FIG. 2 illustrates the change in compressive modulus of a metal foam body according to the present invention after a series of uniaxial compressions along different axes. [Figure 27] (a) Engineering strain of low carbon metal foam extracted from digital image correlation (c) Engineering strain of low carbon metal foam extracted from digital image correlation (a,c,f) (f) Engineering strain of low carbon metal foam extracted from digital image correlation (a,c,f) (b) Corresponding force-stroke (d) Stress-strain curve. [Figure 28]Figure 1 shows a hypothesized strain stiffening mechanism. (a) Schematic stress-strain curve. (b) Schematic stress-strain curve. (c) Schematic stress-strain curve. (d) Schematic illustration of the porosity of a metal foam according to the present invention at three different length scales. (e) SEM images (second and third images) of an actual metal foam sample after the first compression cycle. [Figure 29] (a) Stress-strain measurements on metal foam samples spanning the complete range of elasticity, yield and densification as the samples are repeatedly released. (b) A detailed view of the stress-strain curve of (a) in the measured elastic region. (c) The resulting elastic modulus E from the measurements in (a) plotted against strain. (d) The resulting elastic modulus plotted against the solids content ratio of the samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0105] The scope of the present invention should not be limited by the specific embodiments described herein. Indeed, various modifications of the present invention in addition to those described herein will be apparent to those skilled in the art from the above description and accompanying drawings. Accordingly, such modifications are intended to be included within the scope of the appended claims. Additionally, various references are cited throughout this specification, the disclosures of each of which are incorporated herein by reference in their entirety.
[0106] The aqueous suspension of metal atoms containing precursor particles according to the present invention allows the realization of an extrusion-based 3D printing process for the production of metal foams, e.g. steel or iron based porous structures, with extremely high porosity distributed at three hierarchical levels. The precursor particles also stabilize the foamed ink.
[0107] Using particle-stabilized foams of aqueous suspensions according to the invention as 3D printing inks, pores can be generated on multiple length scales. At the first length scale, porosity can be directly controlled by the printing pattern of the foam filament. At a second, smaller length scale, the gas bubbles of the foamed ink act as templates to form the majority of the mesopores in the printed filament. The structure can be controlled by the concentration and distribution of the bubbles in the ink. At a third, even smaller length scale, porosity results from a heat treatment and optional sintering process that causes a transformation of the suspended precursor particles (e.g., reduction by hydrogen gas in the case of iron oxide particles).
[0108] This includes, for example, moduli of elasticity of over 300 MPa and 1 g / cm, which are consistent with the mechanical efficiency expected for a porous structure. 3 This allows for the production of iron and iron-based alloys having densities less than 10 ....
[0109] An advantageous manufacturing process for such iron-based metal foams is shown diagrammatically in Figure 1. The fabrication of iron-based hierarchical porous structures is a two-step process that involves, in a first step, the preparation of a wet foam ink stabilized by modified particles, and, in a second step, 3D printing the wet foam ink into a three-dimensional structure, followed by reduction and sintering of the dried printed structure.
[0110] Stabilization of wet foams by particles can be achieved by reducing the wettability of the particles in the liquid, thereby facilitating their adsorption to the air / water interface. Particle adsorption reduces the total interfacial area, lowering the free energy of the system. This energy gain can be easily several orders of magnitude larger than the thermal energy, suggesting that adsorption is an irreversible process
[33] . Irreversible particle adsorption renders foams largely immune to common foam destabilization processes such as liquid withdrawal, collapse due to the destruction of lamellar structures, and Ostwald ripening
[34] .
[0111] Oblong magnetite microparticles 11 are functionalized with short chain amphiphilic molecules 12 in Figure 1(a) to produce an aqueous suspension 13 in Figure 1(b). After foaming of the suspension, a foamed ink 1 is obtained containing gas bubbles 14 stabilized by the oblong magnetite particles 11 in Figure 1(c).
[0112] It was experimentally discovered that functionalization of magnetite particles with hexylamine (3 μl per g of particles) provides ideal wettability to promote adsorption at the air / water interface, resulting in a robust and stable foam when air is introduced. To prepare such a stable foam, magnetite particles are first suspended and deagglomerated in water containing the short-chain amphiphilic hexylamine. The polar head group of the positively charged molecule adsorbs to the negatively charged particle surface by electrostatic interactions. This causes the hydrophobic tails of the amphiphile to protrude outwards, making the whole particle slightly hydrophobic. Finally, the desired ultra-stable foam is obtained by mechanically foaming the suspension of modified particles. A particle volume fraction of 50 wt% and an optimized foaming procedure (10 min at 800 rpm) add to the rheological requirements for printing.
[0113] This stabilized viscoelastic ink 1 can then be used in a direct ink writing (DIW) process in Fig. 1(d) for build-up to form a three-dimensional structure 3a. The particle stabilized foamed ink 1 is printed layer by layer by extruding the foamed ink 1 through a print nozzle 21 at room temperature and depositing it as a continuous foam filament 31.
[0114] The DIW approach is particularly suitable for fabricating open cell structures such as grid-like designs and open cell designs.
[0115] There are three rheological requirements for most direct ink writing inks. First, the ink must be shear thinning, which allows the material to flow through the nozzle at low pressure. Second, the ink must have a high yield stress below which the ink will not flow, to ensure that the printed material stays in place. Third, the ink must exhibit a high storage modulus to prevent sagging of the crosslinked filaments within the grid-like structure. For compressible foams, printing conditions must also be adjusted to ensure continuous deposition rather than intermittent extrusion.
[35]
[0116] Even after drying the printed wet foam body 3a, the resulting green body 3b (FIG. 1(e)) retains the foam's cellular structure. The green body 3b is reduced and sintered in a tubular oven 22 under a constant flow of H2 gas (FIG. 1(e)) to yield a highly porous iron foam element 3b (FIG. 1(f)).
[0117] To quantify the rheological behavior and viscoelastic properties of the particle-stabilized wet foam, strain-controlled oscillatory rheological measurements were performed (see Figure 2). The investigated wet foam contained 50 wt% iron oxide particles (50 wt%) and 3 μl hexylamine per gram of iron oxide. The foam shows a clear viscoelastic response with a storage modulus plateau at low strain and a clear yield stress (see Figure 2). The measured yield stress of 70 Pa is not far from the recommended range for DIW inks (100–5000 Pa)
[36] . With a high plateau storage modulus of 4.86 kPa, the foam is still stiff enough to enable direct ink writing of grid-like structures.
[0118] DIW printing of the viscoelastic wet foam using an extrusion-based tabletop printer equipped with a syringe and a nozzle size of 0.84 mm results in the three-dimensional object 3a (see FIG. 3). To create the hierarchical structure, a grid-like design was chosen where the printing path controls the size of the open cells. The open cells are hereafter referred to as macropores 32. Such macropores constitute the first level of hierarchical porosity of the metallic material according to the present invention.
[0119] The ability to print distortion-free grids confirms the appropriate rheological properties of the ink and indicates that the wet foam is resistant to the high shear forces applied during extrusion-based printing that would otherwise cause phase separation and bubble collapse. Furthermore, experiments have revealed that the high stability and viscoelasticity of the particle-stabilized wet foam mitigates any compressibility challenges under typical printing conditions.
[0120] After printing, the wet foam object 3a is dried at 60° C. for 1 hour, leaving only the solid precursor particles and residual organic compounds in the grid-like structure of the resulting green body 3b (see FIG. 5(a)). As can be seen in the SEM images of FIG. 5(b) and FIG. 5(c), drying results in the formation of a second hierarchical level of structure consisting of spherical pores 33 originating from the original foam cells of the wet foam. The dried structure of green body 3b exhibits closed cell porosity with an average pore size of 45.6 μm. These spherical pores are in the intermediate size range and are henceforth referred to as mesopores 33.
[0121] The size of these mesopores can be adjusted by the volume fraction of particles, the concentration of amphiphile, and the foaming rate. In general, increasing the particle and amphiphile content increases the viscosity of the suspension, which reduces the bubble size due to the higher shear stress generated during mechanical foaming. Higher foaming rates can also reduce the bubble size due to the increased shear.
[0122] The green body 3b can be transformed into a hierarchical porous metal body 3c by heat treatment at temperatures ranging from 690 to 1000 °C under a reducing atmosphere. The green body 3b in Figure 5 was heat treated at 850 °C for 30 h under a forming gas flow consisting of 5% H2 and 95% N2. The corresponding temperature profile is shown in Figure 4(a). The XRD spectrum of the fully reduced metal body 3c shows a clear correlation between the expected diffraction peaks for a ferritic (α-Fe) atomic structure, which ensures that the initial magnetite is completely reduced to ferritic iron (see Figure 4(b)). Sintering was performed in parallel to the reduction of magnetite particles to iron particles under the given parameters. Chemical analysis of the reduced sample revealed that the porous iron structure contained 0.204 ± 0.077 wt% carbon, with the organic compounds in the wet foam being the carbon source.
[0123] The combined reduction and sintering process results in a linear shrinkage of about 50%, as can be seen when comparing the metal foam body 3c shown in Figure 6(a) to the green body 3b shown in Figure 5(a). As can be seen in the SEM images of Figures 6(b) and 6(c), reduction and sintering also results in the opening of the closed cell mesopores 32 created during foaming to form micropores 34 within the walls of the mesopores 33 using the bubbles as templates. Combined with the macropores 32 created by the printing route, this results in a unique open cell porous structure with three levels of hierarchical porosity.
[0124] To demonstrate the possibility of adjusting the bubble size and therefore the mesopores of the material according to the invention, the particle concentration of the foam was reduced from 50 wt% as in the above example to 40 wt%, while keeping the amphiphile concentration and foaming procedure constant. It was found that foams with such lower particle concentrations were still sufficiently stiff enough to 3D print grid-like structures. Foams with 40 wt% particles result in larger mesopores with an average diameter of 125.1 μm.
[0125] The reduction process is influenced by several factors including the volume of the sample, the gas flow rate, the H2 and H2O content of the reduction gas, the oxide particle size and the temperature. Depending on the temperature and particle size, the reduction is also accompanied by a sintering process of the metal and metal oxide particles. To explore part of this vast processing parameter space, the effect of different reduction protocols on the microstructure, relative density and mechanical properties of the resulting hierarchical porous materials was investigated. For this purpose, specimens made with the 50 wt% magnetite ink described above were systematically heat treated at 750°C, 850°C and 1000°C for 30 h and optimized conditions (690°C for 40 h). SEM images of the green bodies before reduction and the metal foams after reduction are shown in Figure 7. Several mechanical properties of the samples were investigated and the results are shown in Figures 8(a), 8(b) and 8(c). The symbols used in the plots correspond to the square, circle, diamond and hexagon symbols of each sample in Figure 7.
[0126] Figure 8(a) shows plots of stress-strain curves of the sample reduced and sintered under optimized conditions (sintered at 690°C for 40 hours) in comparison with samples reduced at 750°C, 850°C and 1000°C for 30 hours. Figure 9(a) shows the stress-strain curves of the sample over a wide range of strains and Figure 9(b) shows the elastic modulus and yield strength obtained from the stress-strain data.
[0127] Figure 8(b) shows the absolute and relative compressive moduli (compared to solid materials) plotted against the relative density compared to solid metal. Figure 8(c) shows the yield strength plotted against the relative density compared to solid metal. For comparison, literature data for iron-based printed structures without templated macroporosity are shown. (Grey triangles, Taylor et al.
[26] ; Grey stars, Sharma et al. [7]). The theoretical scaling dependence expected from the open cell foam model is also shown (see LJ Gibson, MFAshby, Proceedings of the Royal Society of London. Series A, Mathematical and Physical Sciences 1982, 382, 43).
[0128] Significant changes can be observed in the microstructure of samples heat treated between 750 and 1000 °C (Figure 7). It was found that heat treatment at 750 °C was sufficient to form micropores in the walls of the mesopores, complementing the foam-like structure of the original green body. At 850 °C, the size of the micropores increases significantly, but the foam-templated mesopores remain visible. When the temperature is increased to 1000 °C, the surface area becomes smaller and the micropores and mesopores merge. This results in an open-cell network with only two levels of hierarchical porosity.
[0129] Accompanying the microstructural change, the determined carbon content drops from 0.20±0.08% C at 850°C to only 0.05±0.01% C at 1000°C. Such reduction is probably caused by the long exposure of high surface area structures to high temperatures, allowing carbon to diffuse out of the material. From this microstructural analysis, it can be concluded that high temperatures should be avoided to preserve the high carbon content and the three levels of hierarchical porosity.
[0130] A particularly advantageous hierarchical steel structure with three levels of porosity was finally obtained by employing a two-step procedure in which the samples were first fully reduced at 690 °C for 40 h, followed by sintering at 850 °C for 2 h, resulting in a microstructure of samples that were reduced at a lower temperature but had thicker struts upon sintering.
[0131] Mechanical characterization reveals that the elastic modulus and compressive yield strength of the porous metal structures increase with heat treatment temperature (Figs. 8(a), 9(a), and 9(b)). Since the relative densities of all samples remained in a comparable range between 0.053 and 0.268, this stiffening effect can be attributed to a stronger solid network structure formed in the case of samples sintered at higher temperatures. The optimal heat treatment protocol was found to be 0.86 ± 0.03 g / cm. 3 This provides an extremely rigid and strong structure while maintaining a very low average density.
[0132] To compare these hierarchical porous structures with other iron-based porous materials, mechanical data are presented in Ashby-type plots showing the effect of relative density on the elastic modulus and compressive strength of previously reported structures (Fig. 8(b), Fig. 8(c)). It is observed that the presence of three hierarchical levels in the disclosed porous structures, compared to state-of-the-art materials [7, 26], results in a significantly reduced relative density that falls within a previously unreachable parameter range. Importantly, the elastic modulus and compressive strength of the disclosed materials follow a dependence on relative density similar to that observed in the reference structures. This dependence matches well with theoretical predictions for open-cell foams according to the Ashby-Gibson model, suggesting that the presented novel materials combine extremely low weight with maximum achievable properties. By reducing the relative density without sacrificing the predicted properties, the hierarchical porous structures reach the state-of-the-art mechanical efficiency using 30% less solid phase.
[0133] The proposed hierarchical pore design can be extended to a variety of other iron oxides and iron-based alloys. To illustrate this, a hierarchical porous Ni-Fe alloy uses NiO and Fe3O4 particles as inorganic precursors in the initial printable form. Nickel is a common alloying material for steel because it ensures that the steel retains austenite, a tough high-temperature crystal structure.
[0134] The nickel content in the alloy can be precisely controlled by adjusting the relative proportions of oxide powders used in the foam formulation. This was verified by elemental analysis (proton induced x-ray analysis) of the alloy designed to contain 28 wt% (calculated) nickel. After heat treatment of the dried precursor foam, the alloy was found to contain 27.3 wt% Ni atoms. X-ray diffraction analysis confirmed the formation of austenite in the heat treated Ni-Fe alloy (Figure 10). Interestingly, the microstructure of the Ni-Fe porous structure was observed to be independent of the sintering parameters and Ni alloy content (Figure 11).
[0135] Figures 8(d), 8(e) and 8(f) show the results of measurements equivalent to those in Figures 8(a), 8(b) and 8(c) for metal foam samples made using different process temperatures and varying the nickel content in the final metal foam, i.e. 0 wt%, 7 wt%, 14 wt%, 21 wt%, 28 wt% and 35 wt% Ni, with the remainder being Fe. In Figure 8(d), the curve for the 21 wt% Ni sample stops before the sample yields due to technical limitations. Again, all data are compared against literature data obtained for iron-based printed structures without templated macroporosity (grey triangles, Taylor et al.
[26] ; grey stars, Sharma et al. [7]). The theoretical scaling dependence expected from an open cell foam model is also shown (Gibson and Ashby, 1993). Figure 12 shows the (a) relative density, (b) density, (c) modulus of elasticity, and (d) yield strength of the same nickel-iron alloy metal foam for two different sintering temperatures. Figure 13 shows the Weibull distribution of strength for the nickel-iron alloy metal foam of Figure 12 containing 28 wt% Ni and sintered at 1000°C for 30 hours.
[0136] In terms of mechanical properties, measurements show that the addition of nickel significantly improves both the elastic modulus and compressive strength of the porous Fe-based alloy. Similar to the pure iron composition, the presence of three hierarchical porosity levels results in a much lower relative density compared to previously reported iron-based porous materials. This reduction in relative density is achieved without compromising the mechanical efficiency of the porous structure, as the measured mechanical properties still follow the trends expected from theoretical predictions. The presence of nickel in the iron-based alloy was found to increase the elastic modulus of the porous structure by 7.5 times and the compressive strength by 5 times compared to a pure iron equivalent with similar density and processing conditions.
[0137] Iron-based porous structures can be used as pure metal foams, metal oxide foams, or metal-metal oxide mixture foams in a wide variety of applications. Iron oxide foams with controlled chemical composition can be obtained by heat treatment of 3D printed green bodies at intermediate temperatures in the range of 550-650 °C. Heat treatment at 550 °C in air for 2 hours leads to partial oxidation of magnetite to brown maghemite. Red hematite structures can be obtained by heat treatment of 3D printed magnetite foams at 650 °C in air for 2 hours. FIG. 14 shows (from left to right) lightweight, permeable, high surface area 3D printed structures according to such a variation of the invention: unreduced magnetite foam, maghemite foam (brown) obtained by oxidizing magnetite at 550°C for 2 hours, 37 wt% maghemite / 63 wt% hematite foam (red) obtained by oxidizing magnetite at 650°C for 2 hours, and sintered hematite foam (silver) obtained by sintering at 1000°C for 2 hours. These oxide foams are fairly flexible, but the mechanical properties can be improved by the addition of binders or sintering. For example, sintering hematite specimens at 1000°C results in a mechanically stronger porous structure with a smooth and shiny surface with the characteristic silver color of sintered hematite. Such oxide foams could potentially be used as substrates for gas catalysis such as methanol oxidation
[37] , toluene cracking
[38] or formic acid decomposition
[39] .
[0138] The porous metal structure itself exhibits the magnetic properties and electrical resistivity (0.00125 Ωm) inherent to iron.
[0139] Iron / iron oxide mixed porous structures can be obtained by partial oxidation of iron oxide green bodies. The composition of the crystalline phases present in the iron porous structures (850 °C for 30 h) after oxidative corrosion for 1-90 days in phosphate buffer (37 °C) as determined by Rietveld fitted XRD spectra is shown in Figure 15 and Table 1. SEM images of iron-based porous structure samples corroded for 3 days in phosphate buffer (37 °C) after sintering for 30 h at 850 °C are shown in Figure 16. [Table 1] The (a) relative and absolute compressive moduli and (b) relative and absolute yield strengths and (b) relative strengths of iron-nickel based metal foams according to the present invention are shown in FIG. 17 along with literature values (grey triangles, Taylor et al.
[26] ) and theoretical values predicted by Gibson-Ashby for open cell structures.
[0140] The surface areas determined for printed structures prepared from mixed foams containing different percentages of iron oxide particles and heat treated at different reduction / sintering conditions are shown in FIG.
[0141] SEM images of metal foams containing different percentages of iron oxide particles (40 wt%, 45 wt% and 50 wt% iron oxide with respect to iron) and heat treated under different reduction / sintering conditions are shown in Figure 19: (a) 690°C, 40 h with sintering; (b) 1000°C, 30 h; (c) 850°C, 30 h; (d) 815°C, 30 h; (e) 730°C, 30 h; (f) 730°C, 15 h; (g) 650°C, 70 h; (f) before reduction.
[0142] Due to the higher electrical resistivity of the iron / iron oxide hybrid foams compared to their pure iron counterparts (0.7 Ωm at room temperature for 35 wt% iron), these porous materials can be used for resistive heating, e.g., as low-power resistive evaporators. It has been experimentally observed that Joule heating with a power of 3 W is sufficient to heat a cubic porous structure 8 mm wide to a steady-state temperature of 180 °C. The combination of resistive heating and the large surface area of the structure (1 m2) allows for the construction of a porous structure that can be heated with a constant current of 100 W.2 A steady state is reached by balancing with the convection cooling enabled by the saturation current (saturation temperature) and the thermal expansion current (saturation temperature).
[0143] FIG. 20 shows the application of metal / metal oxide foams according to the invention as resistive heating elements, for example for vaporizing liquids on demand. FIG. 20(a) shows the experimental setup for vaporizing liquids by resistive heating. A metal foam body 3c with 35 wt% Fe infused with ethereal oil (limonene, 0.4 ml / g) is clamped between two electrodes 23, 23'. A voltage is applied to the metal foam body outputting a power of 3 W. The inset image on the bottom right shows an infrared image of the area marked with a dotted line. FIG. 20(b) shows a time-lapse infrared image. The average temperature over time within the sampling area marked with a dotted line is shown in FIG. 20(c). The dotted line indicates the time of the snapshot in FIG. 20(b).
[0144] Furthermore, the density of the metal foam structure according to the present invention is very low (1 g / cm 3 less than 1.0 g / cm, making it light enough to swim on the water, which is comparable to the density of pure iron (approximately 8 g / cm). 3 ), which is surprising considering the fact that the hierarchical open-cell structure induced by the reduction procedure acts like a sponge for liquids that can wet the metal surface. Under favorable wetting conditions, at least 0.4 ml / g of liquid is spontaneously absorbed into the porous structure due to capillary forces. It was observed that the capillary forces are strong enough to draw liquid into the micropores as well as into the 3D printed channels.
[0145] Such metal foam bodies can float on water and can therefore be used as environmentally friendly oil absorbents. In the context of the present application, the surface of the metal structure is hydrophobized with fumed silica by dip coating. This hydrophobization procedure makes the surface wettable by oil and other non-polar solvents, ensuring that these liquids are spontaneously absorbed into the porous structure. As can be seen from FIG. 21, such hydrophobized iron foam bodies can very effectively absorb hexane (dyed for better visibility) floating on the water surface. An oil drop 41 on the water surface is absorbed by the metal foam body 3c within 20 seconds. The oil wets the hydrophobized surface of the metal foam and is encapsulated in the micro- and macro-pores of the structure.
[0146] A particular advantage of the use of such porous structures as oil absorbents comes from their ability to float on top of the water, absorbing the oil exactly where it is present. As the oil displaces the air in the pores and channels, the density of the structure increases until it begins to sink. This allows for the cleanup of oil spills, where the oil is encapsulated in a metal body and then deposited on the seabed.
[0147] Another method for producing metal foams according to the invention uses an emulsion-based ink system rather than a wet foam-based ink system. Compared to the wet foam composition, the surfactant concentration is increased by 5-50 times (e.g. 1 mmol / g hexylamine, 0.1 mmol / g octyl gallate). 30-80 vol% of a hydrophobic organic solvent (such as n-octane) is added dropwise while mixing. The pH can be adjusted to the pKa of the surfactant (with NaOH or HCl, respectively) to improve emulsification. Binders such as methylcellulose, PVA (polyvinyl alcohol) and PVP (polyvinylpyrrolidone) can be used to stabilize the resulting emulsion (1-7 g / L). The emulsion-based ink can be processed in the same way as the foams (printed, dried, sintered and reduced). In this case, the macropores arise from the organic solvent droplets in the emulsion, as well as the air bubbles in the foam. A metal foam produced by 3D printing of such an emulsion-based ink system is shown in FIG. 22.
[0148] Furthermore, it has surprisingly been discovered that the porous metal structures according to the invention exhibit special strain stiffening behavior.
[0149] The iron and nickel-iron alloy foams were subjected to strain-stress measurements and the elastic modulus E1 was determined within the proportional range. The measurements were then repeated. Unexpectedly, the elastic modulus E2 was found in this second run to be significantly higher. For the nickel-iron alloy foam with 7 wt% Ni reduced at 850°C for 30 hours, the elastic modulus measured in the first run was E1 = 565 Mpa and the second elastic modulus measured was E2 = 2724 Mpa (see Figure 23). The same effect was observed for all metal foams according to the invention investigated. Figure 24 shows a plot of the relative elastic modulus vs. the relative density (relative to the solid metal) for the two iron foams (process parameter sets R2 and R7 in Table 2) and the nickel-iron alloy foams with 7 wt%, 14 wt%, 21 wt%, 28 wt% Ni (process parameter set R6 in Table 2). All samples show a similar increase in elastic modulus with increasing density.
[0150] The compressive modulus improves by a factor of 2 to 20 after compression along the compression direction for Poisson's ratios less than 0.01. This uniaxial stiffening is not accompanied by a density change of more than 2.5% and is permanent as long as only uniaxial stress is applied (Figures 24 and 25). Changing the direction of the applied stress resets the material and the effect occurs again (Figure 26).
[0151] As can be seen in Figure 23, where the data of the stress-strain measurement of the metal foam is shown, the effect of increasing the elastic modulus is permanent. The sample was repeatedly released and then the measurement was resumed. In contrast to the initial proportional increase resulting in the elastic modulus E1, the elastic modulus E2 observed after the first and all subsequent release and resume cycles was significantly (almost 500%) higher. The sample itself remains undeformed (no increase in cross-sectional area).
[0152] Figures 25(a) and 25(b) show the average modulus and density of three metal foams (four samples each) with different solids contents determined in the first, second and third measurement runs. Unless otherwise stated, the solids content always refers to the weight percentage of magnetite powder. For all metal foam types, both values increase with the number of runs. However, the increase in density does not exceed 2.5%. Figure 25(c) shows the corresponding results in a plot of relative modulus vs. relative density. The ratio of modulus after the second and first runs is shown in Figure 25(d), while Figure 25(e) shows the corresponding density ratio. Figure 25(f) shows these values in a plot of modulus ratio vs. density ratio. The results are shown in Figures 25(c) and 25(f) as lines plotted by Ashby, E. spec =c1ρ spec 2 (where c1=1).
[0153] The strain stiffening effect is uniaxial. Figure 26 shows the elastic modulus determined in a series of uniaxial stress-strain measurements (marked with circled numbers 1-8) along different axes, namely the XY plane (Z axis), the YZ plane (X axis), the XZ plane (Y axis) and the normal to the XY plane (Z axis) of a metal foam body specimen. The strain stiffening effect occurs independently along all three axes X, Y, Z. Interestingly, the strain stiffening effect is permanent when the compression axis is unchanged (see Figure 23), but seems to be reset after compression along all three axes, and the strain stiffening effect occurs a second time, as shown by measurement pair 7, 8.
[0154] FIG. 27 shows the results of measurements on metal foam specimens to investigate the local stiffening along the direction of stress application. A first metal foam specimen (low carbon steel with a relative density of 0.11, treated at 850° C.) is subjected to two compression cycles (1) and (2). The measured force is plotted against the stroke length (dotted line in FIG. 27(b)). In both compression cycles, digital image correlation (DIC) shows in a color map (see FIG. 27(a)) the engineering strain along the compression direction at a force value of 70 N, the compression axis being along the vertical line of the drawing. A second metal foam specimen (low carbon steel with a relative density of 0.22, treated at 1000° C.) is subjected to two compression cycles (1) and (2) and the measured force is plotted against the stroke width (solid line in FIG. 27(b)). Again, in both compression cycles, DIC strain images are obtained at a force value of 40 N (FIG. 27(c)).
[0155] FIG. 27(d) shows the measured stress-strain curve for a third metal foam sample (low carbon steel with a relative density of 0.21, treated at 850° C. and with a centrally drilled 3.5 mm diameter hole) along with two subsequent compression cycles (1) and (2). The resulting compressive modulus is shown in FIG. 27(e). The corresponding DIC image of the dimensionless engineering strain along the compression direction is shown in FIG. 27(f). The hole acts to show the local strain stiffening in response to the defect.
[0156] Without wishing to be bound by any particular theory, it is hypothesized that the strain stiffening effect occurs due to the superposition of stress responses at two different length scales, as shown in Figure 28 (see Figure 28(a,b,c)). During compression, the local stress forces are large enough to induce a densification of the micropores within the walls of the macropores (see Figure 28(d,e)). This change is plastic and increases the connectivity of the macropore walls, thereby affecting the overall compressive response. Since the microstructural densification occurs locally, it is anisotropic and only affects the elastic modulus in the compression direction.
[0157] FIG. 29(a,b) shows stress-strain measurement curves for a metal foam sample (low carbon steel with a relative density of 0.22, processed at 850° C.) over the complete range of elasticity, yield and densification upon repeated release of the sample. FIG. 29(c) shows the values of elastic modulus E obtained from the measurements as a function of applied strain; FIG. 29(d) shows the values of elastic modulus E obtained in the elastic region as a function of the solids fraction of the sample. As can be seen, E is approximately 0.01 times larger than E. apparent The maximum E true During the first compression, the stress-strain curve appears to include the standard elastic phase, yielding, and subsequent densification observed in foamed materials. However, the elastic phase is only pseudoelastic. The annular compression reduces the true elastic modulus E seen during the second compression. true It can be seen that the modulus of elasticity increases logarithmically with compressive stress until it reaches a value of . This effect occurs without significant overall densification, and is more precisely the effect of microstructural refinement.
[0158] Ag 97 Nanoporous gold structures obtained by dealloying Au3 are known to exhibit similar effects at the nanoscale and high porosity [40, 41]. However, such effects have not previously been known to exist in microstructures with lower porosity in the micrometer length scale range, such as can be obtained with the metal foams of the present invention, nor at such low strains (<5%).
[0159] Materials and Methods Ink preparation: An aqueous suspension of 40-50 wt% metal oxide powders (magnetite, Fe3O4, E8840, DOWA; green nickel(II) oxide, 99%, ABCR GmbH) and 3 μl / g hexylamine (99%, ACROS Organics) was stirred at 2000 rpm on a THINKY (登録商標) The mixture was homogenized by ball milling with alumina balls (1-5 mm diameter) in a mixer (ARE-250) for 6 min (2 times with 3 min intervals to avoid overheating). Standard compositions contained 50 wt% magnetite powder. The slurry was then foamed at 800 rpm by an electronic stirrer (Heidolph, RZR 2102) until the desired stiffness was achieved (5-15 min). The resulting foam was left overnight in a sealed container and then volume printed by a modified Fused Filament Fabrication (FFF) printer (Ultimaker2+) using a 20 mL syringe and a conical nozzle (0.84 mm diameter). The printing speed is set at 10 mm / s and the extrusion speed is manually adjusted (100-150%) to achieve maximum print quality. A commercial skin cream (NIVEA) was added to prevent the sample from sticking. (登録商標) PMMA plates coated with 1,2-dichlorophenyl ether (PAH) were used as substrates. The final samples were dried at room temperature overnight and in an oven at 60° C. for 1 h.
[0160] Reduction of the printed structures: The samples were reduced in a quartz tube oven (Gero, SR-A 100-500 / 12) with a forming gas flow (95% N2 and 5% H2, Pangas) of 12 l / min. Different heating protocols (Table 2) were used to investigate the effect of the reduction and sintering conditions on the microstructure and properties of the resulting porous metals (see Figures 7 and 8). [Table 2]
[0161] Oxidation of printed structures: As-printed magnetite foam was oxidized to different oxide phases by heating the test material (Naberthem, LE6 / 11 / P300) at 650°C, 750°C or 1000°C for 2 hours (see Figure 14). In addition to thermal oxidation, porous iron structures were also partially oxidized in wet state by placing them in Dulbecco's Phosphate Buffered Saline (Sigma) at 37°C for 1-90 days (see Figure 16, Table 1).
[0162] Surface hydrophobization: The hierarchical porous structures were hydrophobized by dip-coating the specimens in a suspension of 1 wt% hydrophobic fumed silica (Wacker, HDK H18) in hexane (>95%, Sigma) and then drying the coated samples at room temperature in vacuum (see FIG. 21).
[0163] Microstructural characterization: High-resolution SEM images of the pre- and post-reduced foams were taken by scanning electron microscope (LEO1530 instrument, Zeiss GmbH, Germany).
[0164] Compositional characterization: X-ray diffraction spectra were collected by a powder diffractometer (PANalytical Empyrean) equipped with a CuKα X-ray tube (15 kV, 40 mA) and a monochromator. Samples were prepared by crushing into a powder if brittle or compressing the samples into a flat sheet if tough. Particle-Induced X-ray Emission (PIXE) measurements were performed by Max Dobeli at the Laboratory of Ion Beam Physicss, ETH Zurich. Carbon content of iron samples was measured by a carbon / sulfur analyzer (LECO CS230) using four samples of 1 g per composition.
[0165] Mechanical characterization: Compressive strength and modulus were measured by a universal mechanical testing machine (AGS-X, Shimadzu) equipped with a 1000N load cell. To ensure parallel facing surfaces, the specimens were polished to shape (Struers, LaboPol-25, 1000 grit SiC paper) using ethanol as a lubricant to prevent oxidation of the samples. Tests were performed applying a constant displacement rate of 12 mm / min. The raw data was corrected to take into account the mechanical compliance of the testing machine. The mechanical compliance was measured using a 9x9x8 mm aluminum cube as a placeholder. The data was analyzed using Matlab. (登録商標) The compressive yield strength reported was determined by the 0.2% offset method.
[0166] Surface area characterization: N2 gas sorption measurements were performed using a pore size analyzer (Quantachrome Autosorb iQ) at 77 K. Prior to the measurements, the samples were degassed in vacuum at 80 °C for 24 h. Surface areas were determined by the Brunauer-Emmett-Teller method.
[0167] Absorption experiments: The oil absorption capacity of the hydrophobized porous iron structures (see Figure 21) was evaluated by contacting the water-floating samples with hexane (>95%, Sigma) as absorbent, which was stained purple with both Nile Red (Merck) and Methylene Blue (Merck) at 0.01 g / L.
[0168] Electrical conductivity and resistive heating experiments: The resistive heating capability of the partially oxidized porous iron structures (see Figure 21) was evaluated by sandwiching the samples with copper tape and passing an electric current through them using a laboratory power supply (EA-PS-3032-05-B). The temperature of the samples was measured with infrared imaging (IRCAM, Millenium 327k S / M). R-(+)-Limonene (Merck) was used as the vaporizing agent.
[0169] The scope of the present invention should not be limited by the specific embodiments described herein. Indeed, various modifications of the present invention in addition to those described herein will be apparent to those skilled in the art from the above description and accompanying drawings. Accordingly, such modifications are intended to be included within the scope of the appended claims. Additionally, various references are cited throughout this specification, the disclosures of each of which are incorporated herein in their entirety. [Explanation of symbols]
[0170] 1 Foamed aqueous suspension, wet form ink 11 Precursor Particles 12 Surfactant molecules 13 water 14 Air bubbles, foam cells 21 Printing nozzle 22 Tubular oven 23, 23' electrode 3a Three-dimensional structure 3b Green body 3c Metal form element 31 Foam Filament 32 First-level pores, macropores 33 Second-level pores, mesopores 34 Third-level pores, micropores 41 Oil drop References [1] L.-P.Lefebvre, J. Banhart, DCDunand, Adv.Eng.Mater.2008, 10, 775. [2] J.Erlebacher, MJAziz, A.Karma, N.Dimitrov, K.Sieradzki, Nature 2001, 410, 450. [3] MECox, DCDunand, Mat Sci Eng a-Struct 2011, 528, 2401. [4] E. Linul, L. Marsavina, PALinul, J. Kovacik, Compos Struct 2019, 209, 490. [5] MHSun、SZHuang、LHChen、Y.Li、XYYang、ZYYuan、BLSu、Chem Soc Rev 2016、45、3479. [6] N.Kleger、M.Cihova、K.Masania、ARSTudart、JFLoffler、Adv Mater 2019、31. [7] P.Sharma、PMPandey、Mater Design 2018、160、442. [8] R.Orinakova、R.Gorejova、ZOKralova、L.Haverova、A.Orinak、I.Maskal ́ova、M.K upkova、M.Dzupon、M.Balaz、M.Hrubovcakova、T.Sopcak、A.Zubrik、M.Orinak、Appl Surf Sci 2020、505. [9] S.Ray、U.Thormann、M.Eichelroth、M.Budak、C.Biehl、M.Rupp、U.Sommer、T.El Khassawna, FIAlagboso, M. Kampschulte, M. Rohnke, A. Henss, K. Peppler, V. Linke, P. Quad beck、A.Voigt、F.Stenger、D.Karl、R.Schnettler、C.Heiss、KSLips、V.Alt、Biomaterials 2018、157、1.
[10] Y.Conde、JFDespois、R.Goodall、A.Marmottant、L.Salvo、C.San Marchi、A.Mortensen、Adv Eng Mater 2006、8、795.
[11] ARStudart, A. Nelson, B. Ivanovsky, M. Kotyrba, AAKundig, FHDalla Torre, UTGonzenbach, LJGauckler, JFLoffler, Journal of Materials Chemistry 2012, 2012, 2020.
[12] Y.J.Quan, F.M.Zhang, H.Rebl, B.Nebe, O.Kessler, E.Burkel, Mat Sci Eng a-Struct 2013, 565, 118.
[13] A.E.Jakus, N.R.Geisendorfer, P.L.Lewis, R.N.Shah, Acta Biomater 2018, 72, 94.
[14] A.R.Studart, Chemical Society Reviews 2016, 45, 359.
[15] A.R.Studart, R.M.Erb, R.Libanori, Hybrid and Hierarchical Composite Materials, DOI:10.1007 / 978-3-319-12868-9_8(Eds:C.-S.Kim, C.Randow, T.Sano), Springer International Publishing 2015, Chapter 8, 287 pages.
[16] B.Gorny, T.Niendorf, J.Lackmann, M.Thoene, T.Troester, H.J.Maier, Materials Science and Engineering:A 2011, 528, 7962.
[17] L.S.Bertol, W.K.Junior, F.P.d.Silva, C.Aumund-Kopp, Materials&Design 2010, 31, 3982.
[18] L.Yang, O.Harrysson, D.Cormier, H.West, H.Gong, B.Stucker, JOM 2015, 67, 608.
[19] LEMurr、SMGaytan、F.Medina、H.Lopez、E.Martinez、BIMachado、DHHernandez、L.Martinez、MILopez、RBWicker、J.Bracke、Philosophical Transactions of the Royal Society, Physical and Physical AP: Engineering Sciences 2010、368、1999.
[20] P.Heinl、L.Muller、C.Korner、RFSinger、FAMuller、Acta Biomater.2008、4、1536.
[21] C.Xu、QHWu、G.L'Esperance、LLLebel、D.Therriault、Mater Design 2018、160、262.
[22] M.Calvo、AEJakus、RNShah、R.Spolenak、DCDunand、Adv Eng Mater 2018、20.
[23] AEJakus、SLTaylor、NRGeisendorfer、DCDunand、RNShah、Adv Funct Mater 2015、25、6985.
[24] BYAhn、D.Shoji、CJHansen、E.Hong、DCDunand、JALewis、Adv.Mater.2010、22、2251.
[25] SLTaylor、AEJakus、RNShah、DCDunand、Adv.Eng.Mater.2017、19、1600365.
[26] SLTaylor、AEJakus、RNShah、DCDunand、Adv Eng Mater 2017、19.
[27] C.Minas、D.Carnelli、E.Tervoort、ARSTudart、Adv Mater 2016、28、9993.
[28] C.Minas、J.Carpenter、J.Freitag、G.Landrou、E.Tervoort、G.Habert、ARStudart、Acs Sustain Chem Eng 2019、7、15597.
[29] DGMoore、L.Barbera、K.Masania、ARStudart、Nature Materials 2020、19、212.
[30] L.Alison、S.Menasce、F.Bouville、E.Tervoort、I.Mattich、A.Ofner、ARStudart、Sci Rep-Uk 2019、9.
[31] MRSommer、M.Schaffner、D.Carnelli、ARStudart、Acs Applied Materials&Interfaces 2016、8、34677.
[32] C.Kenel、NRGeisendorfer、RNShah、DCDunand、Addit Manuf 2021、37.
[33] R.Murakami、S.Kobayashi、M.Okazaki、A.Bismarck、M.Yamamoto、Front Chem 2018、6.
[34] UTGonzenbach、ARStudart、E.Tervoort、LJGauckler、Angewandte Chemie-International Edition 2006、45、3526.
[35] H.Ovaici、MRMackley、GHMcKinley、SJCrook、J Rheol 1998、42、125.
[36] D.Kokkinis、M.Schaffner、ARStudart、Nat Commun 2015、6.
[37] M.Bowker、EKGibson、IPSilverwood、C.Brookes、Faraday Discuss 2016、188、387.
[38] X.H.Zou、T.H.Chen、H.B.Liu、P.Zhang、D.Chen、C.Z.Zhu、Fuel 2016、177、180.
[39] S.A.Halawy、S.S.Al-Shihry、M.A.Mohamed、Catal Lett 1997、48、247.
[40] S.Shi、Y.Li、B.N.Ngo-Dinh、J.Markmann、J.Weissmuller、Science 371、1026~1033(2021).
[41] B.Zandersons、L.Luhrs、Y.Li、J.Weissmuller、Acta Mater 2021、215、116979.
Claims
1. An aqueous suspension for producing a porous metal structure, comprising: A mixture of 2-49 vol % of at least one compound containing a metal atom, the at least one compound being solid at room temperature, having the form of a powder, and suspended in water; 10 per mol of the compound containing a metal atom -9 ~0.1 mol of surfactant Including, the aqueous suspension is part of a foam and / or the aqueous suspension is part of an oil-in-water emulsion comprising 30-90 vol. % of a lipophilic phase free of polymerizable compounds, Aqueous suspension.
2. 2. The aqueous suspension of claim 1, wherein one or more of the compounds containing metal atoms are compounds that are reducible to a metal in a gaseous atmosphere.
3. 3. The aqueous suspension according to claim 1 or 2, wherein the mixture of at least one compound containing a metal atom is a metal oxide powder.
4. 4. The aqueous suspension of claim 3, wherein the metal oxide powder is Fe. 3 O 4 or NiO or a mixture thereof.
5. 5. The aqueous suspension of claim 4, wherein the particles of the metal oxide powder have a prolate shape.
6. 2. The aqueous suspension of claim 1, wherein one or more of the compounds containing a metal atom is a metal hydride.
7. 7. The aqueous suspension of claim 6, wherein the metal hydride is TiH x , PdH x , ZrH x or MgH 2 1. An aqueous suspension comprising:
8. 2. The aqueous suspension of claim 1, wherein one or more of the compounds containing a metal atom are metal carbonyl compounds.
9. 9. The aqueous suspension according to claim 8, wherein the metal carbonyl compound is Rh 2 (CO) 8 Or Ru(CO) 5 1. An aqueous suspension comprising:
10. 10. An aqueous suspension according to any one of claims 1 to 9, wherein the surfactant is a cationic surfactant or a non-ionic surfactant.
11. 11. An aqueous suspension according to any one of claims 1 to 10, comprising 1 to 7 g / l of binder.
12. 12. An aqueous suspension according to claim 11, wherein the binder is methylcellulose, PVA (polyvinyl alcohol) or PVP (polyvinylpyrrolidone) or a mixture thereof.
13. 1. A method for making a porous metal material, comprising: - providing an aqueous suspension according to claim 1 comprising a mixture of at least one compound containing a metal atom; - foaming said aqueous suspension to convert it into a foam and / or emulsifying said aqueous suspension with a lipophilic compound to convert it into an oil-in-water emulsion containing 30-90 vol. % of a lipophilic phase, free of polymerizable compounds; - forming a three-dimensional structure with said foam or emulsion; - drying said three-dimensional structure to produce a dry structure; - exposing the dried structure to process conditions that convert the compound containing a metal atom into a metal to produce a metal structure; The method includes:
14. The method of claim 13 , wherein the metal structure is sintered.
15. 15. The method of claim 13 or 14, wherein one or more of the compounds containing metal atoms are compounds reducible to a metal in a gas atmosphere, and the dry structure is reduced by exposure to a reducing atmosphere to produce a metal structure.
16. 16. The method of claim 15, wherein the reduction is performed with 0.5 to 100 vol.% H 2 The method is carried out in an inert gas atmosphere.
17. 17. The method of claim 13, wherein one or more of the compounds containing metal atoms are interstitial metal hydrides, and the dry structure is exposed to a temperature at which the hydrogen is released as hydrogen gas to produce a metal structure.
18. 18. The method according to any one of claims 13 to 17, wherein the treating step to produce the metal structure and the sintering step are carried out in one process step.
19. 19. The method of any one of claims 13 to 18, wherein the three-dimensional structure is formed by additive manufacturing, e.g. three-dimensional printing.
20. The method according to any one of claims 13 to 19, wherein the surface of the metal structure is hydrophobized or oleophilized.
21. 21. The method according to any one of claims 13 to 20, wherein after the reduction step, the metal structure is at least partially oxidized.
22. 22. A material made by the method of any one of claims 13 to 21.
23. 23. Use of a material according to claim 22 as a resistive heating element.
24. 23. Use of a material according to claim 22 as a cooling element.
25. 23. Use of a material according to claim 22 for absorbing water-borne lipophilic substances.
26. 23. Use of a material according to claim 22 as a heterogeneous catalyst or a support structure for a heterogeneous catalyst.
27. 23. Use of a material according to claim 22 as an electrode.
28. 23. Use of a material according to claim 22 as a component of an alkaline electrolysis.
29. 23. Use of a material according to claim 22 as a reservoir for gases, in particular molecular hydrogen.
30. 23. Use of a material according to claim 22 as a filtering element.
Citation Information
Patent Citations
Improvements in the manufacture and production of porous metals or metal oxides
GB339645A
Porous sintered metal-containing materials
US20060211802A1
Ultrastable Particle-Stabilized Foams and Emulsions
US20090325780A1
Methods for fabricating three-dimensional metallic objects via additive manufacturing using metal oxide pastes
US20150035209A1
Particle-stabilized foams using sustainable materials
US20210130244A1